In situ monitoring of the structural change of microemulsions in simulated gastrointestinal conditions by SAXS and FRET - Xia Lv; Shuguang Zhang; Huipeng Ma; Peipei Dong; Xiaodong Ma; Ming Xu; Yan Tian; Zeyao Tang; Jinyong Peng; Haibo Chen; Jianbin Zhang (Elsevier, 2018)
Microemulsions are promising drug delivery systems for the oral administration of poorly water-soluble drugs. However, the evolution of microemulsions in the gastrointestinal tract is still poorly characterized, especially the structural change of microemulsions under the effect of lipase and mucus. To better understand the fate of microemulsions in the gastrointestinal tract, we applied small-angle X-ray scattering (SAXS) and fluorescence resonance energy transfer (FRET) to monitor the structural change of microemulsions under the effect of lipolysis and mucus. First, the effect of lipolysis on microemulsions was studied by SAXS, which found the generation of liquid crystalline phases. Meanwhile, FRET spectra indicated micelles with smaller particle sizes were generated during lipolysis, which could be affected by CaCl2, bile salts and lecithin. Then, the effect of mucus on the structural change of lipolysed microemulsions was studied. The results of SAXS and FRET indicated that the liquid crystalline phases disappeared, and more micelles were generated. In summary, we studied the structural change of microemulsions in simulated gastrointestinal conditions by SAXS and FRET, and successfully monitored the appearance and disappearance of the liquid crystalline phases and micelles. KEY WORDS: Microemulsions, SAXS, FRET, Lipolysis, Mucus, Liquid crystalline phase